PERANCANGAN ARSITEKTUR ENTERPRISE PADA MTS SALAFIYAH SYAFIIYAH PUTRI MENGGUNAKAN METODE TOGAF ADM - Akhlis Munazilin; Risma Nur Kholishah; Nur Sahila Chapsah (CV. Denasya Smart Publisher, 2025)
The development of information technology demands that educational institutions have integrated and well-managed information systems to support the effectiveness and efficiency of the educational process. MTs Salafiyah Syafi'iyah Putri (MTs Ibrahimy Sukorejo), as an Islamic boarding school-based educational institution, faces challenges in managing its information system, which is still not fully integrated. This research aims to design an Enterprise Architecture as a basis for developing an information system aligned with the needs and objectives of the madrasah. The method used in this research is TOGAF ADM (The Open Group Architecture Framework - Architecture Development Method). The stages applied include the Preliminary Phase, Architecture Vision, Business Architecture, Application Architecture, Technology Architecture, and Opportunities and Solutions. The research results in the form of an Enterprise Architecture blueprint design that encompasses business, application, data, and technology architecture. This design is expected to serve as a strategic reference in the development of an integrated, efficient, and sustainable information system at MTs Salafiyah Syafi'iyah Putri.